Programación televisiva del canal calidad tv y su incidencia en el desarrollo e identidad cultural de las niñas y niños del Sector 28 de Julio en el cantón El Empalme, año 2019 - Arteaga Zambrano, Silvia Maribel (2020)
This project is based on an analysis of the influence that Calidad TV has in the development of children's cultural identity, which is learnt much more about our Ecuador and the traditions of the community, by doing this it begins to emerge cultural diversity, it must be taken into account that social inclusion, whether disabled or gender discrimination are important at any time, especially nowadays. But we must insist on the violence that exists in the media, no matter the type, and this influences the behavior of infants at home and at school. The problem lies in how the programming of the Calidad TV channel affects the development of the cultural identity of the girls and boys of the sector 28 de Julio in El Empalme, the general objective is to analyze the incidence of the quality channel programming of Calidad TV in the development of the cultural identity of girls and boys in the sector 28 de Julio in the El Empalme city. For this, several research tools have been used, such as the inductive and deductive methods, and the types of research as descriptive and in the field. Surveys were carried out on children and adults in el sector 28 de Julio of El Empalme, province of Guayas For this purpose, the production of advertising capsules is proposed with the objective of having themes about the ancestral customs of the city.